Green space indicators in a social-ecological system: A case study of Varanasi, India. (September 2020) - Verma, Pramit; Singh, Rishikesh; Bryant, Christopher; Raghubanshi, Akhilesh Singh
Highlights: India will add the highest number of urban residents by 2050. Built area, open space, literacy and workers were identified as indicators of green space Literacy positively influenced green space availability Built area of 76 % and open spaces of 5.6 % were suggested as thresholds for land use. Sustainable urban planning will need to include interaction of multiple urban elements. Abstract: From an ecological perspective, quantification indicators of urban green space distribution and accessibility have been the focus of only a few studies. To determine the thresholds of various urban drivers influencing the extent of green spaces was the major objective of this study. We selected Varanasi, a typical city having transition-features of a rapidly growing million-plus city, as a model using a multivariate approach. The ward level differences with literates, workers, population density, household density, per-capita green space, open spaces, built area and green spaces were found to be non-linearly distributed. Indicators for green spaces were identified using the Generalized Additive Model (GAM). Varanasi showed a variation of per capita green-spaces from 0 to 59.95 m 2 at the ward level. Green-spaces showed a large negative correlation with population density (τ = −0.5), household density (τ = −0.5) and built area (τ = −0.7). Sustainability thresholds for built land use and open spaces were identified as 49–76 % and 5.6 %, respectively. Provision of greenspaces even in very small amounts and education based on a local environmental perspective is essential in creating a sustainable urban landscape. The threshold values of identified indicators can help in devising a "safe operating space" for sustainable and healthy urban landscape planning, worldwide.